(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In this article, under the conditions of light gray soil of the Kashkadarya region, as a result of the influence of the method of covering the seeds of winter wheat varieties with bentonite clay and irrigation methods on the rood mass, in the Shukron variety up to 32,9-54,2 g and in the Turon variety up to 40,2-68 g.